Generation of filament-winding paths for complex axisymmetric shapes based on the principal stress field. (1st February 2017) - Fu, Jianhui; Yun, Jaedeuk; Jung, Yoongho; Lee, Deugwoo
Abstract: Filament winding is a process in which glass or carbon fibers are wound around a mandrel to form fiber-reinforced structures of a desired shape. The strength of the fiber-reinforced part is maximized when the fiber direction coincides with the direction of the major principal stress of the part. Previous studies addressed methods to calculate the winding paths of maximum strength by adjusting the mandrel shapes. However, these methods are not appropriate for predetermined shapes that are fixed to satisfy certain special requirements. This study proposes a method to generate filament-winding paths using the principal stress fields of the part to be manufactured. In this method, variable winding directions as close as possible to the major principal stress directions of the product are calculated to generate filament-winding paths that can support the maximum load without slippage. The proposed method had the advantage of not being limited by the complexity of axisymmetric mandrel shape.